Racial Disparities in Care Interactions and Clinical Outcomes in Black Versus White Nursing Home Residents With Dementia. Issue 3 (12th July 2022) - Resnick, Barbara; Van Haitsma, Kimberly; Kolanowski, Ann; Galik, Elizabeth; Boltz, Marie; Ellis, Jeanette; Behrens, Liza; Eshraghi, Karen
Abstract : Background: With the increase in Black nursing home residents, racial and ethnic disparities in quality of care have been raised. Purpose: The purpose of this study was to evaluate racial disparities in care and outcomes over 12 months. Methods: This was a secondary data analysis using data from the Evidence Integration Triangle for Behavioral and Psychological Symptoms of Dementia study. A total of 553 residents, 24% Black residents and 76% White residents, from 55 nursing homes were included. Results: Differences favoring Black resident were noted in agitation, quality of life, inclusion of person-centered care approaches in care plans, and fewer falls and hospitalizations. Differences in quality-of-care interactions favored White residents. There were no differences in depression, resistiveness to care, function, pain, or transfers to the emergency department. Conclusions: Disparities in clinical outcomes were small and generally favored Black versus White residents except for quality-of-care interactions.